Five get into trouble - Blyton, Enid (Hodder Children's Books London, 2001)
The Famous Five are distraught! Dick has been kidnapped - mistaken for somebody else! The gang finally track him down - to a lonely, abandoned house - but then they too are seized and held captive! Now that all of them are miles from home, and from help, how will the intrepid Five get themselves out of this mess?